Estimation Error of Earnings Information: A Test of Representativeness and Anchoring-adjustment Heuristic - Habbe, Abdul Hamid (International Journal of Economics and Financial Issues, 2017)
The main objective of this research is to examine representativeness and anchoring-adjustment on investors’ over/under reaction to earnings information, and the consequence this has on earnings estimation and stock valuation. In particular, the over/under reaction creates an over response to the earnings information that is persistent in the long-term and an under reaction to the earnings information that changes extremely in the short-term. This research was designed with a 2x2x4, full factorial. Data was analyzed by repeated measures ANOVA within-subject. Twenty post-graduate Master students were participants in the experimental. The experimental revealed that investors relied heavily on previous earnings and made the level and pattern of the previous earnings their initial belief (anchor). They overreact on the current earnings information when confirming the fundamental beliefs, and they also overreacted toward persistent earnings. The results of the study confirmed that the overreaction behavior was due to of representativeness heuristic bias. On the contrary, the participant of the experiment underreacted towards the current earnings information when disconfirming the fundamental beliefs, and also underreacted towards the pattern of earnings that show extreme change. The underreaction happens because of anchoring-adjustment heuristic bias. Consequently, when the previous and current earnings have low (high) persistence earnings trend, they underestimated (overestimated) to the future earnings or made error in earnings estimation and underpriced (overpriced) to the securities accordingly or mispriced. It can also be concluded that the error of earnings estimation and stock mispricing is a consequence of the usage of representativeness or anchoring-adjustment heuristic, and indicates that psychological perspective can explain post Earnings Announcement Drift (PEAD) in the capital market. Keywords: Representativeness and Anchoring-adjustment Heuristic, Overreaction and Under Reaction, Error of Earnings Estimation and Share Mispriced, Post Earnings Announcement Drift JEL Classifications: M41, G02